Screening for SH3TC2 gene mutations in a series of demyelinating recessive Charcot‐Marie‐Tooth disease (CMT4). Issue 3 (September 2016) - Piscosquito, Giuseppe; Saveri, Paola; Magri, Stefania; Ciano, Claudia; Gandioli, Claudia; Morbin, Michela; Bella, Daniela D.; Moroni, Isabella; Taroni, Franco; Pareyson, Davide
Abstract: Charcot‐Marie‐Tooth disease type 4C (CMT4C) is an autosomal recessive (AR) demyelinating neuropathy associated to SH3TC2 mutations, characterized by early onset, spine deformities, and cranial nerve involvement. We screened 43 CMT4 patients (36 index cases) with AR inheritance, demyelinating nerve conductions, and negative testing for PMP22 duplication, GJB1 and MPZ mutations, for SH3TC2 mutations. Twelve patients (11 index cases) had CMT4C as they carried homozygous or compound heterozygous mutations in SH3TC2 . We found six mutations: three nonsense (p.R1109*, p.R954*, p.Q892*), one splice site (c.805+2T>C), one synonymous variant (p.K93K) predicting altered splicing, and one frameshift (p.F491Lfs*32) mutation. The splice site and the frameshift mutations are novel. Mean onset age was 7 years (range: 1–14). Neuropathy was moderate‐to‐severe. Scoliosis was present in 11 patients (severe in 4), and cranial nerve deficits in 9 (hearing loss in 7). Scoliosis and cranial nerve involvement are frequent features of this CMT4 subtype, and their presence should prompt the clinician to look for SH3TC2 gene mutations. In our series of undiagnosed CMT4 patients, SH3TC2 mutation frequency is 30%, confirming that CMT4C may be the most common AR‐CMT type.